PREDICTING PREDICTING THE INTENTION OF PURCHASE OF COSMETIC PRODUCTS IN ISLAMIC COLLEGE STUDENTS IN BANYUMAS INDONESIA WITH HALAL LABELS AND THEORY PLANNED BEHAVIOR - Parno, Parno; Sulasih, Sulasih; Novandari, Weni (Indonesian Scientific Journal of Islamic Finance, 2024)
Cosmetics are products that can not be separated in everyday life. When planning a purchase is influenced cosmetics are products by several factors. This study uses the Theory of Planned Behavior, which is a theory that explains that behavior is formed because of intentions/interests that are influenced by attitudes, subjective norms, and behavioral control. In addition, this study uses the halal label as another independent variable. So the purpose of this study was to determine the effect of attitudes, subjective norms, behavioral control, and halal labels on the intention to purchase cosmetic products in Islamic Religious College Students in Banyumas, Indonesia. This research uses quantitative research methods. The population is Islamic Religious College Students in Purwokerto. The number of samples used is 397 respondents. The sample collection technique used probability sampling by means of proportionate stratified random sampling and other techniques, namely nonprobability sampling by means of purposive sampling. This research was analyzed by multiple linear regression methods. The results of this study indicate that partially and simultaneously attitudes, subjective norms, behavioral control, and halal labels have a positive effect on purchase intentions Keywords: Attitude; Subjective Norms; Behavioral Control; Halal Labels; Intention Purchase